The role of Old Believers' enterprises: Evidence from the nineteenth century Moscow textile industry - Danila Raskov; Vadim Kufenko (Universität Hohenheim, 2014)
The early accumulation of capital and the pioneering of capitalist enterprise have been undertaken in many countries by heterodox religious communities. The role of the Old Believers (further OB) in the early development of Russian industry and trade was noted by many economic historians (Blackwell, 1965; Gerschenkron, 1970; Beliajeff, 1979; Stadnikov, 2002; Kerov, 2004; Raskov, 2012); however, empirical and statistical research on the topic is still scarce. Therefore one of our goals is to analyze the role of the OB entrepreneurship in a dynamic dimension using statistical data. Taking advantage of official censuses of 1850, 1857 and, what is more important, 15 archive sources for confessional data for 1808 - 1905 and 7 industrial reports, we analyze the role of the OB firms in the Moscow textile industry for the period of 1832 - 1890. We find that the share of the OB firms in turnover and employment was over-proportionate prior to 1879, which hints at a higher propensity to entrepreneurship. The turnover per worker of the OB firms was significantly higher only in the wool sub-sector. Additionally, the OB firms tended to employ more labor. We capture the continuous process of the rise and fall of the OB entrepreneurship, especially in cotton-paper and wool weaving sub-sectors. Bearing in mind cyclical waves of repressions against the OB, we can state, that the performance of their firms was impressing. We discuss the Weber thesis and the Petty-Gerschenkron argument, and state that various factors contributed to their success: working ethics and minority status; social capital, networking and access to interest free financing; own informal institutions and reputation mechanisms; human capital and literacy.
urn:nbn:de:bsz:100-opus-9791
Keywords: N33; N83; J15; L26; Z10; 330; economic history of Russia; the Old Believers; religious minority; minority entrepreneurship; textile industry